Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) dalam Meningkatkan Keterampilan Kolaboratif Peserta Didik Pada Mata Pelajaran SKI Kelas XB MAN Sidenreng Rappang - Harjuna, Masita (IAIN Parepare, 2024)
Collaborative skills are very important competencies for students in the 21st century, which play a role in equipping them to work together in teams, communicate effectively, and face the challenges of social life and the world of work. Cooperative learning using the Teams Games Tournament (TGT) model is one approach that can improve students' collaborative skills. This study aims to examine the effectiveness of implementing the TGT model in improving collaborative skills in the subject of Islamic Cultural History (SKI) in class X B MAN Sidenreng Rappang. The approach used is qualitative with a case study type of research, involving observation, interviews, and documentation. The results of the study indicate that the implementation of the TGT model can improve students' collaborative skills, including communication, cooperation, and empathy. This model creates an interactive and enjoyable learning atmosphere, encouraging students to be more active in discussing, sharing ideas, and working together in groups. In addition, the implementation of TGT also strengthens social values, such as respecting differences, which are very important in building positive character in students. These findings suggest that the TGT model is effective in creating an inclusive learning environment and can be implemented to improve the quality of classroom learning, as well as prepare students for future social and academic challenges.